Development of Subject-Specific Proximal Femur Finite Element Models Of Older Adults with Obesity to Evaluate the Effects of Weight Loss on Bone Strength - Schoell, SL (J Osteoporos Phys Act, 2018)
STUDY BACKGROUND: Recommendation of intentional weight loss in older adults remains controversial, due in part to the loss of bone mineral density (BMD) known to accompany weight loss. While finite element (FE) models have been used to assess bone strength, these methods have not been used to study the effects of weight loss. The purpose of this study is to develop subject-specific FE models of the proximal femur and study the effect of intentional weight loss on bone strength. METHODS: Computed tomography (CT) scans of the proximal femur of 25 overweight and obese (mean BMI=29.7 ± 4.0 kg/m(2)), older adults (mean age=65.6 ± 4.1 years) undergoing an 18-month intentional weight loss intervention were obtained at baseline and post-intervention. Measures of volumetric BMD (vBMD) and variable cortical thickness were derived from each subject CT scan and directly mapped to baseline and post-intervention models. Subject-specific FE models were developed using morphing techniques. Bone strength was estimated through simulation of a single-limb stance and sideways fall configuration. RESULTS: After weight loss intervention, there were significant decreases from baseline to 18 months in vBMD (total hip: −0.024 ± 0.013 g/cm(3); femoral neck: −0.012 ± 0.014 g/cm(3)), cortical thickness (total hip: −0.044 ± 0.032 mm; femoral neck: −0.026 ± 0.039 mm), and estimated strength (stance: −0.15 ± 0.12 kN; fall: −0.04 ± 0.06 kN). Adjusting for baseline bone measures, body mass, and gender, correlations were found between weight change and change in total hip and femoral neck cortical thickness (all p<0.05). For every 1 kilogram of body mass lost cortical thickness in the total hip and femoral neck decreased by 0.003 mm and 0.004 mm, respectively. No significant correlations were present for the vBMD or strength data. CONCLUSION: The developed subject-specific FE models could be used to better understand the effects of intentional weight loss on bone health.